Temperature distribution analysis of monocrystalline photovoltaic panel for Photovoltaic-Thermoelectric generator (PV-TEG) hybrid application - Ruzaimi A.; Shafie S.; W. Z. W. Hassan; N. Azis; M. Effendy Ya'acob; E. Elianddy (Institute of Advanced Engineering and Science, 2020)
An experiment has been carried out to prove the practicality of converting the waste heat from PV panels into electrical energy by observing the temperature levels and distribution of a conventional monocrystalline silicon (Mono c-Si) photovoltaic (PV) panels for photovoltaic-thermoelectric generator (PV-TEG) hybrid application of a Hybrid Agrivoltaic (HAV) Greenhouse System project. From the observation, highest temperature of the PV backside panel surface reached 81.1°C during solar noon and expected to reach even higher during hot season. The highest power output from the 160 numbers TEG modules in series and parallel configuration were calculated to reach 119 Watt during that time at ΔT 56.1 °C. This output is expected to fluctuate over the weather temperature fluctuation throughout the day. Meanwhile, for the heat distribution, it is best to apply the TEG arrays with optimized PV angle setup, where the temperature seems to be distributed evenly at all time, to provide optimum heat source to the TEG modules. It was concluded that the excess heat from the bottom surface of PV panels can be utilize by converting the heat via temperature differential to harvest additional electrical energy by integrating TEG system, hence maximizing the potential of solar radiation capacity in generating clean renewable energy.